Design and application of a novel dielectric loaded helical antenna to WLAN products - Mohammad Ezanuddin, Abdul Aziz; Azremi, Abdullah Al Hadi; Soh, Ping Jack; Anuar, Mat Safar (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org